ALTERED TGF-ϐ SIGNALING IN A SUB-POPULATION OF HUMAN STROMAL CELLS PROMOTES PROSTATIC CARCINOGENESIS - Franco, Omar E (2011)
Carcinoma-associated fibroblasts (CAFs) play a critical role in malignant progression. Loss of TGF-ϐ receptor II (TGFϐR2) in the prostate stroma is correlated with prostatic tumorigenesis. To determine the mechanisms by which stromal heterogeneity due to loss of TGFϐR2 might contribute to cancer progression, we attenuated TGF-ϐ signaling in a subpopulation of immortalized human prostate fibroblasts in a model of tumor progression. In a tissue recombination model, loss of TGFϐR2 function in 50% of the stromal cell population resulted in malignant transformation of the non-tumorigenic human prostate epithelial cell line BPH1. Mixing fibroblasts expressing the empty vector and dominant negative TGFϐR2 increased the expression of markers of myofibroblast differentiation [co-expression of vimentin and alpha smooth muscle actin (αSMA)] through elevation of TGF-ϐ1 and activation of the Akt pathway. In combination, these two populations of stromal cells recapitulated the tumor inductive activity of CAFs. TGFϐR2 activity in mixed stromal cell populations cultured in vitro caused secretion of factors that are known to promote tumor progression, including TGF-ϐ1, SDF1/CXCL12, and members of the FGF and BMP families. In vivo, tissue recombination of fibroblasts overexpressing TGF-ϐ1 and SDF1/CXCL12 not only induced transformation of BPH1 cells, but also promoted a robust growth of highly invasive cells, similar to effects produced by CAFs. While the precise nature and/or origin of the particular stromal cell populations in vivo remain unknown, these findings strongly link heterogeneity in TGF-ϐ signaling to tumor promotion by tumor stromal cells.